Trehalose as an indicator of desiccation stress in Drosophila melanogaster larvae: a potential marker of anhydrobiosis - Thorat, Leena J.; Gaikwad, Sushama M.; Nath, Bimalendu B. (Biochemical and Biophysical Research Communications, 2012)
In the current scenario of global climate change, desiccation is considered as one of the major environmental stressors for the biota exposed to altered levels of ambient temperature and humidity. Drosophila melanogaster, a cosmopolitan terrestrial insect has been chosen as a humidity-sensitive bioindicator model for the present study since its habitat undergoes frequent stochastic and/or seasonally aggravated dehydration regimes. We report here for the first time the occurrence of anhydrobiosis in D. melanogaster larvae by subjecting them to desiccation stress under laboratory conditions. Larvae desiccated for ten hours at <5% relative humidity could enter anhydrobiosis and could revive upon rehydration followed by resumption of active metabolism. As revealed by FIR and HPLC analyzes, our findings strongly indicated the synthesis and accumulation of trehalose in the desiccating larvae. Biochemical measurements pointed out the desiccation-responsive trehalose metabolic pathway that was found to be coordinated in concert with the enzymes trehalose 6-phosphate synthase and trehalase. Further, an inhibitor-based experimental approach using deoxynojirimycin, a specific trehalase inhibitor, demonstrated the pivotal role of trehalose in larval anhydrobiosis of D. melanogaster. We therefore propose trehalose as a potential marker for the assessment of anhydrobiosis in Drosophila. The present findings thus add to the growing list of novel biochemical markers in specific bioindicator organisms for fulfilling the urgent need of environmental biomonitoring of climate change. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Anhydrobiosis; biomarker; Deoxynojirimycin; Desiccation; Drosophila melanogaster; trehalose